DIGITAL PHILANTHROPY AND SUSTAINABLE DEVELOPMENT ECOSYSTEMS: A CASE STUDY OF ONLINE LITERACY PRACTICES IN AN INDONESIAN ZAKAT INSTITUTION - Eko Muliansyah (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study investigates the transformative role of digital philanthropy and online literacy practices within an Indonesian zakat institution, framing philanthropy as a critical actor in sustainable development ecosystems. Employing a qualitative literature-based case study approach, augmented by systematic document and media content analysis of institutional publications, social media, and mass media reports, the research synthesizes global literature with Indonesian scholarship. Findings reveal that digital philanthropy in Indonesia actively contributes to sustainable development goals by strategically channeling Islamic philanthropy for societal impact and national welfare. Digital platforms facilitate enhanced stakeholder collaboration, fostering greater engagement and transparency. The study also illuminates the opportunities and challenges for governance within this digital ecosystem, highlighting issues such as data protection, accountability, and the need for robust regulatory frameworks. Theoretically, this research reframes philanthropy as an ecosystem-based development actor, emphasizes the transformative impact of digitalization, and enriches global discussions by integrating unique Indonesian perspectives on sustainable development, collaborative governance, and Islamic social finance. This offers an empirically grounded understanding of how cultural heritage, technological innovation, and development aspirations intersect in a significant Global South context.